Coordination of trivalent lanthanum and cerium, and tetravalent cerium and actinides (An = Th(iv), U(iv), Np(iv)) by a 4-phosphoryl 1H-pyrazol-5-olate ligand in solution and the solid state. Issue 10 (19th February 2021) - Zhang, Jianfeng; Wenzel, Marco; Schnaars, Kathleen; Hennersdorf, Felix; Schwedtmann, Kai; März, Juliane; Rossberg, André; Kaden, Peter; Kraus, Florian; Stumpf, Thorsten; Weigand, Jan J.
Abstract : Single crystal X-ray analyses, solution NMR and EXAFS studies of a series of f-elements metal(iv ) complexes of a 4-phosphoryl pyrazolone ligand show essentially the same coordination of the metal ions in solution and in the solid state. Abstract : Structural investigations of three actinide(iv ) 4-phosphoryl 1 H -pyrazol-5-olate complexes (An = Th(iv ), U(iv ), Np(iv )) and their cerium(iv ) analogue display the same metal coordination in the solid state. The mononuclear complexes show the metal centre in a square antiprismatic coordination geometry composed by the two O-donor atoms of four deprotonated ligands. Detailed solid state analysis of the U(iv ) complex shows that dependent on the solvent used altered arrangements are observable, resulting in a change in the coordination polyhedron of the U(iv ) metal centre to bi-capped trigonal prismatic. Further, single crystal analyses of the La(iii ) and Ce(iii ) complexes show that the ligand can also act as a neutral ligand by protonation of the pyrazolyl moiety. All complexes were comprehensively characterized by NMR, IR and Raman spectroscopy. A single resonance in each of the 31 P NMR spectra for the La(iii ), Ce(iii ), Ce(iv ), Th(iv ) and Np(iv ) complex indicates the formation of highly symmetric complex species in solution. Extended X-ray absorption fine structure (EXAFS) investigations provide evidence for the same local structure of the U(iv ) and Np(iv ) complex in toluene solution, confirming the observations made in the solid state.